Compensation:: The American Way - Azevedo, Ross; Scoville, James (Journal of Comparative International Management, 2001)
This paper depicts a picture of American compensation systems and practices in light of concerns for equitable treatment of workers. It raises questions about these practices in reference to racial, gender, and executive pay levels in the U.S., and points out that the principle of equity applied regularly has fallen short when interests and needs of particular groups have been examined. Addressing this shortfall in relation to equity concerns is the key policy challenge facing the American compensation manager.